The acceptability and feasibility of an internet-administered, guided, low-intensity cognitive behavioural therapy intervention for parents of children treated for cancer: findings from a qualitative study involving public contributors - Ella Thiblin; Johan Lundgren; Mattias Bergqvist; Tho Huynh; Christina Reuther; Sandra Rösler; Joanne Woodford; Louise von Essen (BMC Psychiatry)
Abstract Background Despite parents of children treated for cancer commonly reporting psychological difficulties such as symptoms of depression and anxiety, there is a lack of evidence-based psychological interventions tailored to their needs. We therefore developed an internet-administered, guided, low-intensity cognitive behavioural therapy-based self-help intervention (EJDeR). We examined the acceptability and feasibility of the intervention and study procedures in the single-arm feasibility trial ENGAGE. Results suggested the intervention and study procedures are feasible and acceptable. However, a need for modifications and refinements to the intervention and study procedures was identified. We conducted a qualitative interview study to explore the acceptability and feasibility of the intervention and study procedures from the perspective of parents to inform modifications and refinements to the intervention and study procedures. Methods Semi-structured interviews were conducted with 52 parents (17 fathers, 35 mothers). A public contribution group (three parents of children treated for cancer) analysed the data independently from the research team and contributed to dissemination. An inductive content analysis was performed using the Framework Method. Results The intervention was perceived as acceptable and relevant, and parents expressed positive attitudes toward internet-administered support. However, parents identified a need for adaptations to intervention content, e.g., a greater focus on the family, trauma, and the cancer experience. Barriers to engagement were also identified, including technical difficulties and a need for modifications to improve intervention user-friendliness and smartphone and/or tablet compatibility. Study procedures were also perceived as acceptable and feasible. However, a need was identified to improve parents’ understanding of the study and to reduce the amount and frequency of assessments. The public contributors’ analysis was similar to that of the research team. However, the research team overlooked important nuances. For example, the public contributors’ analysis highlighted parents’ difficulties distinguishing between the intervention and study procedures. Conclusions The intervention and study procedures were perceived as acceptable and feasible. However, the need for important modifications and refinements were suggested to improve future acceptability and feasibility. Involving public contributors in the analysis resulted in developing a more comprehensive and nuanced understanding of the data. Trial registration ISRCTN 57,233,429 (Registration date: 19/04/2018); ISRCTN 18,404,129 (Registration date: 25/11/2019).